A Systematic Literature Review of the Mobile Application for Object Recognition for Visually Impaired People - Nor Hisham Z.A.; Faudzi M.A.; Ghapar A.A.; Rahim F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mobile computing; Search engines; Smartphones; Assistive technology; Mobile applications; Mobile platform; Mobile Technology; Systematic literature review; Systematic literature review (SLR); Visual impairment; Visually impaired people; Object recognition